تأثير شكل الوصلة اللحامية على طاقة الصدم وقيم القساوة في منطقة التأثر الحراري عند صيانة آليات شركة مرفأ اللاذقية - وسام قدار; خضر خفيف; علي حسن (Tishreen University, 2018)
Maintenance operation of marine machines and structures in Latakia Port Company is effective and done periodically. Electric arc welding is the basic procedure in maintenance operations where replacing the plates that lose thickness or that exposed to failure because of corrosion or hitting the landing platform. Choosing the best welding parameters and the joint shape that suits each case (according to operating conditions and the place of the plate in the machine and loads type that the joint is exposed to) is important for obtaining the best possible properties. In this paper specimens of an old metal (lift's platform) and of the new metal that's used in replacing in Port Company was taken. Welding joints was done in six ways (Xold-old , Xold-new ,  Kold-new , Knew-old , Vold-old , Vold-old). Hardness test, impact test and 'dynamic loads test using solidworks program' were done. Hardness values change along heat affected zone for each joint and the change of impact energy values according to joint shape diagrams were drawn. Stresses and strains values the specimens exposed to in each case of joints shapes V, K, X was calculated using ٍSolidworks program. Results were compared and discussed. The results showed that there is a relationship between joint shape and HAZ width and also between HAZ width and impact energy. That makes it possible to predicate Impact energy that joints can resist before failure consequently expect the loads that achieve safe usage. Also choosing the most suitable joint shape for joints exposed to this kind of loads is possible. تأثير شكل الوصلة اللحامية على طاقة الصدم وقيم القساوة في منطقة التأثر الحراري عند صيانة آليات شركة مرفأ اللاذقية عملية الصيانة في شركة مرفأ اللاذقية عملية فعالة وتتم بشكل دوري على مختلف الآليات البحرية والمنشآت. عملية اللحام باستخدام القوس الكهربائي هي الإجراء الأساسي في أغلب عمليات الصيانة حيث يتم استبدال الألواح التي تتناقص سماكتها أو التي تتعرض لتلف نتيجة التآكل أوالإرتطام بالرصيف البحري. اختيار بارامترات اللحام الأفضل وشكل الوصلة المناسب لكل حالة )بحسب ظروف الخدمة وتوضع اللوح في الآلية البحرية ونوع الحمولات التي تتعرض لها هذه الوصلة( هام من أجل الحصول على أفضل خواص ممكنة. تم في هذا البحث أخذ عينات من معدن قديم (منصة قاطر) ومن المعدن الجديد المستخدم في التعويض في شركة المرفأ. تم تنفيذ الوصلات اللحامية بست طرق وهي :( Xold-old , Xold-new ,  Kold-new , Knew-old , Vold-old , Vold-old) تم إجراء اختبار القساوة واختبار الصدم و'اختبار الحمولة الديناميكية باستخدام برنامج 'solidworks وتم رسم مخططات تغير قيم القساوة على طول منطقة التأثر الحراري لكل وصلة ومخطط تغير طاقة الصدم بحسب شكل الوصلة وكذلك حساب قيم الإجهادات وقيم الإنفعالات التي تتعرض لها العينات في حالات أشكال الوصلات X-K-V باستخدام برنامج solidworks وتمت مقارنة ومناقشة النتائج. بينت النتائج وجود علاقة بين شكل الوصلة وعرض منطقة التأثر الحراري وأيضاً بين عرض منطقة التأثر الحراري وطاقة الصدم. وهذا يمكن من التنبؤ بقيمة طاقة الصدم التي تتحملها العينات قبل أن تنهار وبالتالي معرفة قيمة الحمولات التي تحقق الإستخدام الآمن. كذلك يمكن اختيار شكل الوصلة الأكثر ملائمة للقطع التي تتعرض لهذا النوع من الحمولات الديناميكية.